Pado, a fluorescent protein with proton channel activity can optically monitor membrane potential, intracellular pH, and map gap junctions - Kang, Bok Eum; Baker, Bradley J. (NATURE PUBLISHING GROUP, 2016)
An in silico search strategy was developed to identify potential voltage-sensing domains (VSD) for the development of genetically encoded voltage indicators (GEVIs). Using a conserved charge distribution in the S2 alpha-helix, a single in silico search yielded most voltage-sensing proteins including voltage-gated potassium channels, voltage-gated calcium channels, voltage-gated sodium channels, voltage-gated proton channels, and voltage-sensing phosphatases from organisms ranging from mammals to bacteria and plants. A GEVI utilizing the VSD from a voltage-gated proton channel identified from that search was able to optically report changes in membrane potential. In addition this sensor was capable of manipulating the internal pH while simultaneously reporting that change optically since it maintains the voltage-gated proton channel activity of the VSD. Biophysical characterization of this GEVI, Pado, demonstrated that the voltage-dependent signal was distinct from the pH-dependent signal and was dependent on the movement of the S4 alpha-helix. Further investigation into the mechanism of the voltage-dependent optical signal revealed that inhibiting the dimerization of the fluorescent protein greatly reduced the optical signal. Dimerization of the FP thereby enabled the movement of the S4 alpha-helix to mediate a fluorescent response.
Keywords: VOLTAGE-SENSING DOMAIN; MONOMERIC RED; NEURONS; PROBE; TRANSMISSION; SENSOR; CELLS